If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3a + -4) = -84 Reorder the terms: 3(-4 + 3a) = -84 (-4 * 3 + 3a * 3) = -84 (-12 + 9a) = -84 Solving -12 + 9a = -84 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 9a = -84 + 12 Combine like terms: -12 + 12 = 0 0 + 9a = -84 + 12 9a = -84 + 12 Combine like terms: -84 + 12 = -72 9a = -72 Divide each side by '9'. a = -8 Simplifying a = -8
| 7a^2-14a=21 | | -8(7k+1)=216 | | 5x-2x*x=2 | | logx+logx^4=5 | | 3v^2-36=3v | | (9/10)/3 | | 12=-8x-4x | | (x-1)(x-2)(x-3)(x-4)=24 | | 21=1+3k-8k | | 22=1+4p-7 | | 13=5(1+4M)-2 | | 2/7-1/7=3/14 | | 8x-7y+17=0 | | (6y-5p)(y)=(3p)(2p) | | [(2q-3r)-5][(2q-3x+5)]= | | 5(2x-5)=1.5(18x+40) | | 8cos(2x)=5 | | 32-5m= | | 5(v-8)-6=-4(-5v+9)-7 | | (t-4)(4)+(t-1)(4)=(5)(t-1)(t-4) | | sinx=(x^2)/(625pi^2) | | 7=2b-8+1 | | 7.6x-3.4=11.8 | | -5(3n+3)=10 | | (T-9)(T+64)=0 | | 7.5x-1.6=13.4 | | (t+4)(4)+(t+4)(4)=(t-4)(t+4)(5) | | 6.6x-1.3=11.9 | | 4(3z+1)-5(z+8)=3(z+1) | | 1/t-4 | | 21=6-3a-3 | | 8k-4k=0 |